ANALISIS PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KARKAS AYAM BROILER DI PASAR TRADISIONAL KOTA YOGYAKARTA - , CAECILIA LISNAWATY A.K, Dr. Tri Anggraeni Kusumastuti, SP., MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted to analyze the income of broiler carcass retailer, the contribution income to total household income and also the influence of scale on sales, cost of purchasing equipment, transportation cost, bussiness period, use of service slaughter, and business location on income of broiler carcass retailer at traditional markets in Yogyakarta City. This research was done from August to September 2013. Location selection was done by purposive sampling and chosen the traditional market in Yogyakarta City, there were Beringharjo, Kranggan, Demangan, and Lempuyangan Market. Determination of respondent carried out a cencus that taken all of broiler carcass retailer at Beringharjo, Kranggan, Demangan, and Lempuyangan Market. The factors that influence income of broiler carcass retailer were determined with multiple linear regression analysis. Average income of broiler carcass retailer was IDR 3,699,572.05/month for small scale on sales, IDR 6,533,740.94/month for medium scale on sales, and IDR 11,623,451.64/month for big scale on sales. It contributed total household income about 80.10% for small scale on sales, 89.79% for medium scale on sales, and 93.39% for big scale on sales. Multiple linear regression analysis showed that the coefficient determination (R2) was 0.898 means that 89.80% factors that influence income of broiler carcass retailer could be explained in terms together by scale on sales, cost of purchasing equipment, transportation cost, bussiness period, use of service slaughter, and business location. The independent variable scale of sales positively and significantly (P<0,01), bussiness period positively and significantly (P<0,05), and cost of purchasing equipment negatively and significantly (P<0,01) influence income of broiler carcass retailer at traditional markets Yogyakarta City.